Photosynthetic Response of an Alpine Plant, Rhododendron delavayi Franch, to Water Stress and Recovery: The Role of Mesophyll Conductance - Cai, Yanfei; Wang, Jihua; Li, Shifeng; Zhang, Lu; Peng, Lvchun; Xie, Weijia; Liu, Feihu (Frontiers in Plant Science, 2015)
Rhododendron delavayi Franch is an evergreen shrub or small tree with large scarlet flowers that makes it highly attractive as an ornamental species. The species is native to southwest China and southeast Asia, especially the Himalayan region, showing good adaptability and tolerance to drought. To understand the water stress coping mechanisms of R. delavayi, we analysed the plant’s photosynthetic performance during water stress and recovery. In particular, we looked at the regulation of stomatal (gs) and mesophyll conductance (gm), and maximum rate of carboxylation (Vcmax). After four days of water stress treatment, the net CO2 assimilation rate (AN) declined slightly while gs and gm were not affected and stomatal limitation (SL) was therefore negligible. At this stage mesophyll conductance limitation (MCL) and biochemical limitation (BL) constituted the main limitation factors. After eight days of water stress treatment, AN, gs and gm had decreased notably. At this stage SL increased markedly and MCL even more so, while BL remained relatively constant. After re-watering, the recovery of AN, gs and gm was rapid, although remaining below the levels of the control plants, while Vcmax fully regained control levels after three days of re-watering. MCL remained the main limitation factor irrespective of the degree of photosynthetic recovery. In conclusion, in our experiment MCL was the main photosynthetic limitation factor of R. delavayi under water stress and during the recovery phase, with the regulation of gm probably being the result of interactions between the environment and leaf anatomical features.